Monetary policy influences in Australian housing markets - Costello, Greg; Fraser, P.; MacDonald, Garry (Emerald Group Publishing Limited, 2015)
Purpose–This paper aims to analyze the impact of common monetary policy shocks on house prices at national and capital city levels of aggregation, using Australian data and the Lastrapes (2005) two-part structural vector autoregressive (SVAR) empirical method. Design/methodology/approach–The Lastrapes (2005) two-part SVAR empirical method is applied to Australian housing market and macroeconomic data to assess the impact of common monetary policy shocks on house prices. Findings–Results show that while the impact of shocks to interest rates on aggregate house prices is almost neutral, the responses of state capital city house prices to the same shock can exhibit significant asymmetries. Originality/value–This paper contributes to the monetary policy–asset price debate by examining the influence of Australian monetary policy on capital city housing markets over the period 1982-2012. To the authors’ knowledge, this is the first empirical study that has adapted this Lastrapes (2005) methodology to the analysis of housing markets.